Representation and Narration of Migratory Flows and Migrants in the Mediterranean: A Translocal Perspective - Monachino, Dalila; Taronna, Annarita; Moro, Aldo (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
Since the fall of the Berlin wall in 1989, open borders have seemed to facilitate flows of people within Europe. The demographic change within Europe is progressively combining with growing migration flows from non-EU countries. The intertwining phenomena have led the demographic composition of Europe towards a growing complexity and generated a set of challenging issues.. In particular, in recent decades, the incessant increase of migration flows along African-Mediterranean routes have prompted a series of radical social, cultural and linguistic changes, pushing migrants into an already diversified structure. A reading of the current geo-political scenario might help to identify new paths of interpretation and description of a reality in which old and new migration flows have triggered a gradual rethinking of concepts such as language, translation, mobility, contact, nation, identity and community, in a constanteffort of contextualizing them within a thorough analysis of their socio-linguistic and cultural implications. In this sense, the present research1 has the goal of analyzing the linguistic, discursive and narrative modes through which specific issues relating to migration were covered by both private and public local broadcasters in a given period of time. Drawing on the extensive literature on migration studies, the theoretical field of research lies in a transdisciplinary perspective which privileges, for the specific purposes of the proposed research, critical discourse analysis (CDA) as a particularly effective approach for observing whether and how local media use linguistic and discursive patterns that tend to endorse or oppose dichotomous definitions marked by formulas such as "us" and "them", Italian and foreigner, residents and immigrants, etc. In this perspective, particular attention has been placed on some of the crucial topoi concerning immigration and reception: representation of the status of immigrants upon arrival, i.e. whether they are refugees and asylum seekers or illegal immigrants; the acceptance or rejection of landing boats; expectations concerning their integration in the land of arrival. The themes were selected in virtue of their potential contribution to the demystification of the idea of immigration as a unitary phenomenon without contextualized references, elaboration or relational dynamics. This will point the way to a representation of migrants and migration in Puglia as an uneven, ambivalent and editable discourse (Colombo 1999). Finally, it should be noted that critical discourse analysis has been integrated with ethnolinguistics (Davies 2000; Vertovec 2007) which may contribute the renewal of the current lexicon used in the narratives of cross-border mobility across the Mediterranean, with their mixture of transversality and deterritorialization, of "disorientation" and exasperated localism, which indeed require a profound change. Furthermore, the research aimed at finding recurrent rhetorical figures such as metaphors and personifications recalling wilderness, which can be interpreted in the light of the theoretical framework constituted by the work of the linguist George Lakoff (2003). In particular, the identification of epistemological metaphors will help problematizing both the uncritical and sometimes unaware language choices that reporters make, and the obscure meaning such metaphors might have for the audience.